(untitled) (Revista de Ciências Agroveterinárias, 2007)
This study aimed to evaluate the curricula of Veterinary Medicine courses in southern Brazil through documental research. Twenty five courses of Veterinary Medicine were identified, twenty three of which made their curricula available. An analysis of the curricular composition was conducted, based on the Veterinary Medicine professionals’ fields of performance. The following fields of performance were proposed on the study: Veterinary Clinic, Zootechny and Animal Production, and Preventive Veterinary Medicine and Public Health. The curricular analysis revealed that Veterinary courses in southern Brazil use different fields similarly. The basic subjects are a priority on the first and second year of the course. An emphasis on Veterinary Clinic starts growing from the second year on, dominating the time schedule when compared with the other fields of performance. Zootechny and Animal Production had the second best percentage of time schedule and Preventive Veterinary Medicine and Public Health is in last position, with a significantly reduced number of hours in the schedule when compared to the other areas of Medical Veterinary knowledge.